Modeling Australia’s Construction Workforce Demand: Empirical Study with a Global Economic Perspective - Liu, J.; Love, Peter; Sing, Michael; Carey, Brad; Matthews, Jane (American Society of Civil Engineers, 2014)
Workforce planning is vital for implementing strategic human resource planning. A causal model that incorporates a global economic perspective is derived in this paper by undertaking a detailed review of the normative literature and empirically estimated by a vector error correction (VEC) model. The reliability of the developed VEC model is validated by using several tests (e.g., Lagrange multiplier test, White’s test, and Jarque-Bera test), all of which indicate that the proposed models are able to forecast construction workforce demand in the context of global economic turbulence. This paper contributes to the literature by systematically developing advanced models that not only model construction workforce demand, but also examine the impact of the global economic climate on the labor market. It provides policy makers with a practical tool and insight into future workforce demand, which serves to assist to launch an effective human resources strategy in the construction industry.